 The Eduladder is a community of students, teachers, and programmers just interested to make you pass any exams. So we help you to solve your academic and programming questions fast.
Watch related videos of your favorite subject.
Connect with students from different parts of the world.
See Our team
Wondering how we keep quality?
Got unsolved questions?

gate-cse-2011-->View question

Taged users:

Likes:
Be first to like this question

Dislikes:
Be first to dislike this question
Reason is:
1. (AB+AB)=AB(AB′+A′B)′=AB
2. (A(B)+(A)B)=(AB)=AB(A′(B′)′+(A′)′B′)′=(AB)=AB
3. AB+(A)B=ABA′B′+(A′)′B=AB
4. ((AB).(A+B))=(AB)+(A+B)=AB+AB=AB

Likes:
|ShwetaMerchant

Dislikes:
Be first to dislike this answer

### Watch more videos from this user Here

Learn how to upload a video over here

Reason is:
1. (AB+AB)=AB(AB′+A′B)′=AB
2. (A(B)+(A)B)=(AB)=AB(A′(B′)′+(A′)′B′)′=(AB)=AB
3. AB+(A)B=ABA′B′+(A′)′B=AB
4. ((AB).(A+B))=(AB)+(A+B)=AB+AB=AB

Likes:
|ShwetaMerchant

Dislikes:
Be first to dislike this answer

### Watch more videos from this user Here

Learn how to upload a video over here

D.D

Likes:
Be first to like this answer

Dislikes:
Be first to dislike this answer